Influence Gender Equality, Competence, And Disability Discrimination On Job Opportunities Employment Opportunities With E-Recruitment Of Linkedin Application Users - Rendi; Fauzan, Fauzan; Puspita, Veny (Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to determine whether gender equality affects employment opportunities with E-recruitment of Linkedin application users, to determine whether competence affects employment opportunities with E-recruitment of Linkedin application users, to determine whether disability discrimination affects employment opportunities with E-recruitment of Linkedin application users, to determine whether gender equality, competence, and disability discrimination affect employment opportunities with E-recruitment of Linkedin application users. The type of research used is quantitative with an explanatory approach. The population in this study were all Linkedin users. Data collection techniques are literature study, observation, and questionnaires. Based on the research results, the following conclusions can be drawn: 1). There is an effect of gender equality (X1) on employment opportunities with E-recruitment of Linkedin application users (Y) with a significance value of 0.008 <0.05 and tcount> ttable (4.548> 1.65882) thus Ho is rejected and Ha is accepted. 2). There is an effect of competence (X2) on employment opportunities with E-recruitment of Linkedin application users (Y) with a significance value of 0.000 <0.05 and tcount> ttable (4.243> 1.65882) thus Ho is accepted and Ha is rejected. 3). There is an effect of disability discrimination (X3) on employment opportunities with E-recruitment of Linkedin application users (Y) with a significance value of 0.000 <0.05 and tcount> ttable (4.080> 1.65882). Thus Ho is rejected and ha is accepted. 4). The value of Fsig is 0.000 <0.05 and and Fcount> Ftable (15.042> 2.69), so it can be concluded that together gender equality, disability discrimination, competence and promotion affect employment opportunities with E-recruitment of Linkedin application users.